The reconstruction of regional systems of innovation to allow the evolution of the biotechnology industry in non-high technology regions : the case of the Western Cape region in South Africa - Uctu, Ramazan (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.